ETIOLOGY AND MECHANISMS OF ULNAR AND MEDIAN FOREARM NERVE INJURIES - Puzovic, Vladimir; Samardzic, Miroslav; Jovanovic, Milan; Zivkovic, Bojana; Savic, Andrija; Rasulic, Lukas (Vojnosanitetski pregled, 2015)
Aim: Current retrospective cohort study investigated the etiology and mechanisms of median and ulnar forearm nerves injuries. Methods: This study included 99 patients surgically treated in Clinic of Neurosurgery, Clinical Center of Serbia, from January 1st, 2000 to December 31st, 2010. All data are obtained from patients histories. Results: The majority of injured patients were male, 81 (81.8%), while only 18 (18.2%) were females, and majority of them had nerve injuries of distal forearm - 75 (75.6%).In our series there were two injury mechanisms, transection in 85 patients and traction and contusion in 14 patients. The most frequent etiological factor of nerve injuries is cutting, in 61 patients. Nerve injuries are often associated with other injuries. In our study we had 22 vascular injuries, 33 muscle and tendon injuries and 20 bone fractures. Conclusion: The majority of patients with peripheral nerve injuries are represented in the working age population, which is a big socio-economic problem. In our study 66 out of 99 patients were between 17 and 40 years old, in the most productive age. The fact that majority of patients had nerve injuries of distal forearm and that they are operated within first 6 months after injury, gives them good functional prognosis.